Model Manajemen Pembelajaran Dari Rumah Untuk Pendidikan Berkarakter (Studi Pada TK Islam Makarima Dan TK Inklusi Saymara Sukoharjo) - Ria Winanti; Purwanto Purwanto; Khuriyah Khuriyah (Jurnal Ilmiah Ekonomi Islam, 2021)
The current state of education has drastically changed, maintaining virtual learning and teaching, educators adapting to utilizing existing technology by implementing information transformation. The fact shows that educators face problems to be able to present interesting learning for students, and interactive learning, especially learning for early childhood aged 3-4 years (Play Group) and 4-6 years (Kindergarten), so creative teachers are needed. and innovative (Ahmed et al., 2020). The implementation of online learning in PAUD is better known as PAUD from home (PFH). PFH is an early childhood activity held at home by families with children with remote teacher guidance and assistance. Of course, PFH is different from online learning at the elementary, junior high, high school, and university levels. Previously, PAUD services focused more on the relationship between families and schools, then Covid-19 teaches all parties to implement real PAUD by paying attention to the reciprocal relationship between institutions, families, and the environment. This research is carried out with a qualitative approach, with the type of case study, because the research carried out examines one field of study or variables in depth, namely learning management from home. The results of the study show that online learning at the Kindergarten level is not necessarily carried out without careful planning, following the stages of implementing PFH which are carried out in three stages: 1. Preparation stage; this stage starts from checking the condition of the students' families, then choosing the type of learning whether online, offline, or blended learning. Furthermore, preparing children, preparing parents, preparing themed lesson plans, and preparing communication guides between teachers and students' families. 2. Implementation stage; families discuss with children about the activities to be sent, families also look for various learning resources (books, videos, pictures related to themes, etc.), children are free to follow the teacher's ideas or their own ideas, there is interaction, children play, and documentation of activities. 3. Post-implementation stage; families report PFH results by documenting children's activities.